Current Management of Non-Alcoholic Fatty Liver Disease (NAFLD) - Budiman, Benny (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2024)
Non-alcoholic fatty liver disease (NAFLD) is characterized by hepatic steatosis in the absence of other causes of liver fat accumulation. The prevalence of NAFLD is increasing and now among top causes of hepatocellular carcinoma. The diagnosis of NAFLD requires evidence from liver biopsy. There are currently no specific drugs for therapy of NAFLD. Current mainstay for management of NAFLD is lifestyle interventions focused around weight loss. Lifestyle interventions can be done by dietary modification or increasing physical activity level. Pioglitazone and vitamin E are only recommended for patient whom was confirmed NAFLD by liver biopsy. New agents such as obeticholic acid, elafibranor, selonsertib, and cenicriviroc are still waiting for phase III result to be recommended as therapy for NAFLD. Bariatric surgery can be advised for NAFLD patient with obesity who is not adequately controlled by medical therapy.